Pengembangan Media Pembelajaran Visual Novel â€œPlus And Minusâ€ Berbasis Smartphone untuk Materi Bilangan Bulat SMP - Achsanudin Nursy; Atik Wintarti; Nina Rinda Prihartiwi (MATHEdunesa, 2023)
In the current technological era, the use of technology is important in the world of education.Trends in Mathematics and Science Study (TIMSS) 2019 showcases the importance of using learning technology to increase the effectiveness of learning and teaching. Educators need to make adjustments to develop the quality of learning by using technological media in learning. One of them is by using a smartphone. Thus it is necessary to develop media-based learningsmartphone. The purpose of this research is to find out the process and results of the development of instructional media "Plus And Minusâ€ in terms of validity, practicality, and effectiveness. This research is a development research using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The instruments used include media validation sheets for media experts, media validation sheets for material experts, student response questionnaire sheets and learning achievement test sheets. Based on the results of the research that has been done, an average validity value of 3.12 (media expert) and 2.78 (material expert) is obtained so that it can be categorized as learning media "Plus And Minusthis is valid. This learning media trial was conducted on a limited basis to 30 class VII-A students of SMP Negeri 1 Mojowarno to obtain data from practicality (student response questionnaires) and media effectiveness (learning achievement score sheets). The results of the research after being tested and evaluated, that learning media is declared practical with a good category gets a score of 3.02 or a percentage of 75.5%. Effective criteria are obtained from the results of the learning outcomes test scores. Learning media is declared effective with a good category with a percentage value of 60.46667%.